NEGOSIASI DALAM HUKUM ISLAM: - Fauziah, Umi Fajar; MUSONNIF, AHMAD (Ahkam: Jurnal Hukum Islam, 2024)
Fitrah Zakat plays a central role as an obligatory duty that cannot be ignored. Fitrah zakat is a mandatory contribution for every individual in the Muslim community, known as (zakat al-nafs). It must be distributed accurately to those entitled (mustahiq), ensuring the goal of meeting the needs of the mustahiq during festive occasions is achieved. This research is motivated by the zakat distribution practices in Pojok Village, where several hamlets distribute zakat evenly among the local community. The study critically examines the concept of negotiating zakat distribution within Islamic law, particularly through the principle of "harmony." The research employs qualitative and field research methods, gathering data through direct field observations and deductive analysis. Primary data sources include interview results, supplemented by secondary data from relevant literature. Data collection techniques involve observation, interviews, and documentation. Data analysis techniques include data verification and presentation, with data validity ensured through triangulation and extended research.